Typification of the name Ephedra nebrodensis (Ephedraceae) - Del Guacchio, Emanuele; Cambria, Salvatore; Brullo, Salvatore (Phytotaxa, 2021)
Ephedra Tourn. ex Linnaeus (1753: 1040) (Ephedraceae) includes about 80 species occurring worldwide (WCSP 2020 onwards). Ephedra nebrodensis Tineo ex Gussone (1844: 638) is a Macaronesian-Mediterranean nanophanerophyte, growing in dry and rocky places (Pignatti et al. 2017). However, if on one hand the application of this name is unequivocal, on the other hand, when E. major Host (1831: 671) and E. nebrodensis are regarded as synonyms (e.g., Freitag & Maier-Stolte 1993, Bartolucci et al. 2018, WCSP 2020 onwards), the name by Host claims priority. Nevertheless, E. major is a nomen ambiguum (Greuter et al. 1984), considered by some authors as a synonym of E. foeminea Forsskål (1775: 219) (Nouviant 1999), so that Brullo & Del Guacchio (2021) made a formal proposal to reject the name according to Art. 57.1 of the ICN (Turland et al. 2018). Such a proposal, if accepted, automatically will establish E. nebrodensis as the priority name (see WCSP 2020 onwards for a list of heterotypic synonyms).